Opinião pública e comunicação dos riscos socioambientais da transposição do Rio São Francisco em comunidades tradicionais de Sergipe - Becker, Michele Amorim (2016)
This research aims at analyzing the level of participation of traditional communities from the lower São Francisco, particularly the Indigenous Xokó Community and the Quilombola Community of Resina, in the process of communicating socio-environmental risks concerning the transposition of the São Francisco, as well as their contributions to the public opinion in Sergipe concerning this project. This study was conducted in the light of Convention 169 of ILO, concerning indigenous and tribal societies. Two hypotheses shall be proved: first, the low level of participation from traditional communities in the process of communicating socio-environmental risk is caused by a “non recognition” of these social actors as actors of speech, since both the managers of the project and the press from Sergipe refuse to take into account the experiences and perceptions from these communities concerning the river and the environment in which they live. Second, the restriction of these actors when it comes to the public sphere implies a reduction of their influence on the public opinion of Sergipe concerning the transposition. The methodology we used was the participative research, with a qualitative approach. The methodological procedure is divided in three steps: bibliographical research, which is highly important in any scientific enquiry; field research, with an ethnographic emphasis, which allows a better understanding of the social, cultural and work relations the traditional communities hold with the São Francisco; and documental research, which is fundamental to understand the level of participation these communities have in the communicative process. This research has an interdisciplinary character, since it deals with different areas of knowledge, such as environmental sciences, humanities and applied social sciences. The results clarify that, through the entire process of communicating the socio-environmental risks of the transposition, the traditional communities we observed had their right to participation neglected by both the public power and the press. They claim their access to information was minimal, and the only way available for them to communicate with other parts of society consisted of popular manifestations, organized by social movements. Therefore, the restricted access to the public sphere made it impossible for the experiences and perceptions coming from traditional communities to influence the public opinion of Sergipe when it came to the project of transposition of the waters of the São Francisco River, weakening the democratic process.